Die gebildete Frau und die neue Zeit : Eine Gabe an die deutschen Frauen - Decken, E. von der (Historische Quellen zur Frauenbewegung und Geschlechterproblematik ;, 1897)
A wide-ranging discussion of the educated, middle-class German woman at the close of the 19th century. Themes touched upon include the relationship of such a woman to the classes above and below her, philanthropic work, the need for improved education for women at the secondary level, and women within the university system.